2020
DOI: 10.1016/j.rmed.2020.106210
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Targeting MALAT1 and miRNA-181a-5p for the intervention of acute lung injury/acute respiratory distress syndrome

Abstract: Background: ALI/ARDS is a severe lung injury leading to refractory respiratory failure, accounting for high morbidity and mortality. However, therapeutic approaches are rather limited. Targeting long non-coding RNA MALAT1 and microRNA miR-181a-5p might be potential option for ALI/ARDS intervention. Objective: We aimed to investigate the role of MALAT and miR-181a-5p in the pathogenesis of ALI/ARDS, and test the therapeutic effects of targeting MALAT and miR-181a-5p for ALI/ARDS intervention in vitro. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Previous study showed that miR-181a-5p relieves inflammation by targeting endocan in monocrotaline-stimulated pulmonary arterial hypertension [29]. MiR-181a-5p regulates acute lung injury and respiratory distress syndrome [30]. MiR-181a-5p restricts vascular atherosclerosis and inflammation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that miR-181a-5p relieves inflammation by targeting endocan in monocrotaline-stimulated pulmonary arterial hypertension [29]. MiR-181a-5p regulates acute lung injury and respiratory distress syndrome [30]. MiR-181a-5p restricts vascular atherosclerosis and inflammation [31].…”
Section: Discussionmentioning
confidence: 99%
“…PMVECs (pulmonary microvascular endothelial cells) were administrated with lipopolysaccharide (LPS, 50 ng/mL, S1732‐25, Beyotime) to mimic the ALI cell model as previously reported. 11 …”
Section: Methodsmentioning
confidence: 99%
“…miR-23a-3p has also been reported to have a potential of binding to IL-8 3'UTR [75]. miRNAs which are not present in MSCderived exosomes may also play critical roles in prognosis management [81]. For instance, miR-155 acts as a regulator of pro-inflammatory cytokines [82], and it also promotes innate immune responses of miR-155 and miR-128 against respiratory system viruses [83].…”
Section: Identification Of Common Mirnas For Both Variantsmentioning
confidence: 99%